(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The article is devoted to the analysis of direct, scientific, philosophical, mythological, religious and historical sources concerning many questions regarding the possible existence, location, shape, size, features of protection, the reasons for the death of the Garden of Eden and Paradise. The article also raises topical issues of the moral image of modern mankind through the prism of the possible fall of the first people who inhabited Eden in prehistoric times. The article also considered various hypotheses and versions on understanding the use of high, space technologies by "gods", the traces and prints of which were partially deciphered using various scientific research methods, such as methods of comparison, synthesis, analysis, abstraction, mental modeling, inductive and deductive methods, etc. How these methods were effectively applied in the study is described in detail in the article. The described methods helped to discover, if not direct, then indirect evidence, facts of the possible existence in the eastern countries of Asia, in distant antiquity, of a certain formation, similar in descriptions to the Garden of Eden, created with the help of high technologies, not yet discovered by people. The work is of a scientific and theoretical nature and is included in the orbit of fundamental research devoted to this global topic. The author hopes that the theoretical study will help those interested in this problem at least a little closer to the goal. Key words: myths, legends and scriptures of ancient peoples, the Garden of Eden, paradise, inductive and deductive research methods, mental modeling, metatransfer technologies, “Star Gate”.